Bulge fatigue testing of freestanding and supported gold films. Issue 2 (15th January 2014) - Merle, Benoit; Göken, Mathias
Abstract: Abstract : The bulge test was used to investigate the fatigue properties of gold thin films with a thickness between 100 and 300 nm. The membranes were pressurized at a rate of 0.2 Hz up to 10 5 times, during which their stress and strain states were continuously recorded. Gold films on a silicon nitride substrate were cyclically loaded into tension and compression. Due to the presence of the substrate, no membrane failure was observed, but the residual stress shifted from an initially tensile state to an increasingly compressive one. Typical fatigue damage mechanisms consisting of extrusions were found in some large grains. Freestanding films were cyclically loaded in pure tension until failure occurred. The data acquired during the fatigue tests show a strong ratcheting of the films, which is indicative of cyclic plastic creep. Microstructural investigations clearly show grain boundary sliding in very thin films with columnar grains extending through the thickness.